Drosophila CLIP-190 and mammalian CLIP-170 display reduced microtubule plus end association in the nervous system - Beaven, Robin; Dzhindzhev, Nikola S.; Qu, Yue; Hahn, Ines; Dajas-Bailador, Federico; Ohkura, Hiroyuki; Prokop, Anderas (American Society for Cell Biology, 2015)
Axons act like cables, electrically wiring the nervous system. Polar bundles of microtubules (MTs) form their backbones and drive their growth. Plus end–tracking proteins (+TIPs) regulate MT growth dynamics and directionality at their plus ends. However, current knowledge about +TIP functions, mostly derived from work in vitro and in nonneuronal cells, may not necessarily apply to the very different context of axonal MTs. For example, the CLIP family of +TIPs are known MT polymerization promoters in nonneuronal cells. However, we show here that neither Drosophila CLIP-190 nor mammalian CLIP-170 is a prominent MT plus end tracker in neurons, which we propose is due to low plus end affinity of the CAP-Gly domain–containing N-terminus and intramolecular inhibition through the C-terminus. Instead, both CLIP-190 and CLIP-170 form F-actin–dependent patches in growth cones, mediated by binding of the coiled-coil domain to myosin-VI. Because our loss-of-function analyses in vivo and in culture failed to reveal axonal roles for CLIP-190, even in double-mutant combinations with four other +TIPs, we propose that CLIP-190 and -170 are not essential axon extension regulators. Our findings demonstrate that +TIP functions known from nonneuronal cells do not necessarily apply to the regulation of the very distinct MT networks in axons.